2006
DOI: 10.1073/pnas.0603095103
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum aminopeptidase 1 (ERAP1) trims MHC class I-presented peptidesin vivoand plays an important role in immunodominance

Abstract: CD8 ؉ T cells respond to short peptides bound to MHC class I molecules. Although most antigenic proteins contain many sequences that could bind to MHC class I, few of these peptides actually stimulate CD8 ؉ T cell responses. Moreover, the T cell responses that are generated often follow a very reproducible hierarchy to different peptides for reasons that are poorly understood. We find that the loss of a single enzyme, endoplasmic reticulum aminopeptidase 1 (ERAP1), in the antigen-processing pathway results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
167
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 63 publications
7
167
2
6
Order By: Relevance
“…The increase in GSW11 generation occurred despite an overall decrease in MHC I levels; MHC I downregulation is typically observed in ERAAP-knockout cells (Fig. 1D) (11)(12)(13)(14). This confirmed that the generation of GSW11 is ERAAP sensitive.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The increase in GSW11 generation occurred despite an overall decrease in MHC I levels; MHC I downregulation is typically observed in ERAAP-knockout cells (Fig. 1D) (11)(12)(13)(14). This confirmed that the generation of GSW11 is ERAAP sensitive.…”
Section: Resultssupporting
confidence: 68%
“…In humans, two aminopeptidases perform this function, ERAP1 and ERAP2 (7)(8)(9); in mice, only one aminopeptidase exists, ERAAP (10). ERAAP is critical for the generation of many antigenic epitopes in vivo and can influence the generation of the antigenic peptide repertoire (11)(12)(13)(14). ERAAP can also destroy antigenic epitopes by trimming them to lengths too small for MHC binding, thus its characterization as an antigenic peptide editor (12).…”
mentioning
confidence: 99%
“…The latter feature refers to the low ERAP1-trimming activity toward most peptides shorter than eight residues (12,16). Absence of ERAP activity has been shown to drastically change the profile of MHC class I-associated peptides (17) and/or alter Ag presentation in vitro and in vivo in numerous experimental systems (18)(19)(20). ERAP2 has been proposed to have an accessory role in ER peptide trimming, because of its complementary N-terminal specificity (12).…”
Section: P Rocessing Of Ags For Presentation By Mhc Proteins Involvesmentioning
confidence: 99%
“…This trimming is critical for the generation of many antigenic epitopes in vivo and influences the generation of the antigenic peptide repertoire (6)(7)(8). Because the functions of ERAP1 and HLA-B27 intersect in the ER at the final stages of the antigen processing pathway, it is reasonable to postulate that the disease mechanism or pathogenicity arise from defects/variations in the function of molecules that lie on this pathway.…”
mentioning
confidence: 99%